2020
DOI: 10.18267/j.cebr.230
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Hard Commodity Prices Changes on Inflation in European Union Countries

Abstract: This article analyses the impact of the changes in hard commodity prices in the world commodity exchanges on the variation of countries' general price level. In other words, this article aims to determine the impact of hard commodity prices changes on inflation. In this paper, all countries of the European Union (EU) are included in the research, and case analysis is done accordingly. The methodology applied is the following: a study of the recent scientific literature, processing and systemization of statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…The paper also confirms transition of commodity price to inflation in countries with flexible exchange rate system but not for countries adopting the fixed rate system, attesting to the importance of changes in exchange rate in the discourse. Lapinskaite and Miecinskiene (2019) conclude that there is no significant relationship between world commodity prices and fluctuations in general price levels in European Union (EU) countries in the long run. The study however showed that changes in price of natural gas on the international market correlates positively on consumer price inflation of 14 EU countries.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…The paper also confirms transition of commodity price to inflation in countries with flexible exchange rate system but not for countries adopting the fixed rate system, attesting to the importance of changes in exchange rate in the discourse. Lapinskaite and Miecinskiene (2019) conclude that there is no significant relationship between world commodity prices and fluctuations in general price levels in European Union (EU) countries in the long run. The study however showed that changes in price of natural gas on the international market correlates positively on consumer price inflation of 14 EU countries.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Other researchers including Haider et al (2011), Ali and Sassi (2016) and Fazio et al (2018) also focused on the role governance and institutional variables play in inflationary conditions; they identified factors such as corruption control, government effectiveness, political stability and regulatory quality as key elements impacting movement in rate of inflation. Furthermore, there are also studies such as Chen et al (2014), Miecinskiene and Lapinskaite (2014), Sekine and Tsuruga (2018), Tule et al (2019), Lapinskaite and Miecinskiene (2019) and Fasanya and Awodimila (2020) that approach the subject by assessing the influence of commodity prices on rate of inflation in various geographical jurisdictions with varied results. Compared to aforementioned studies, however, this study Inflation uncertainty adopts a different approach in its assessments of factors influencing movements in rate of inflation and inflation uncertainty among economies in the sub-region.…”
Section: Introductionmentioning
confidence: 99%
“…Priežastys, lėmusios infliacijos kilimą, yra įtempta situacija darbo rinkoje (kvalifikuotų darbuotojų trūkumas), pasaulinė COVID-19 pandemija ir staigus energinių išteklių kainų augimas. Infliacija sukelia kainų kilimą, jeigu prekių kainos per žemos, o pasiūla ir paklausa nesubalansuota, pinigai neišvengiamai nusėda gyventojų kišenėse, į cirkuliaciją išleidžiamas papildomas pinigų kiekis ir, kaip šio proceso padarinys, atsiranda infliacija (Bartkienė, 1995) (Lapinskaitė & Miečinskienė, 2020). Medžiagų tiekėjų duomenimis, nerūdijantysis plienas 2022 m. vasario mėn.…”
Section: įVadasunclassified
“…Despite that price becomes one of the important factors for consumers to determine something they will use (Sinolungan, Kimbal, & Kawulur, 2022). As Furlong said in Lapinskaite and Miecinskiene (2019) that non-oil and gas commodity prices can be a leading indicator of inflation because they can respond quickly, especially to increased demand and economic changes due to disasters.…”
Section: Introductionmentioning
confidence: 99%